Brand Communication Strategy Analysis of Lululemon Athletica Using AISAS Model - Sitorus Sitorus; Hilyatussyuhada Hilyatussyuhada; Da Silva; Nurusholih Nurusholih (Jurnal Syntax Transformation, 2023)
Brand communication is an effort done by a brand to promote their unique traits or superiority against other brands, using many kinds of strategy. One of successful examples of brand communication is from lululemon athletica; a brand which focuses on athletic garments from America-Canada that centered in Vancouver. Lululemon is a company that swear and commit on developing sustainability and humane development through their natural and human resources, to the point where lululemon is known as an ideal model of brand for sustainability fashion. This scientific article is written to evaluate and to analyze lululemon athletica’s brand communication strategy using AISAS (Attention, Interest, Search, Action, and Share) analysis model. This research is using the method of qualitative. Data were collected through various sources. Primary data was obtained from observation via internet in the form of posters, videos, and social media activity about lululemon athletica. Secondary data was obtained through literature reviews. Lululemon athletica’s brand communication is focused on transparency, and also the health of both environment and their users; where this strategy resulting in successful trust from their users.